PENGEMBANGAN BLENDED LEARNING MELALUI APLIKASI E-CAMPUS INSTITUT AGAMA ISLAM BUNGA BANGSA CIREBON - Bambang Firmansyah; Sulaiman Sulaiman (Edulead : Journal of Education Management, 2020)
Generational differences are one of the subjects that arise in the development of the world of education, This has an impact on different beliefs, values, culture, perspectives, hobbies, and skills in life and work. The generation that was born in the 1980s to 1995's when the technology development was so fast was called the Y-generation. Based on data from students of the Institut Agama Islam Bunga Bangsa Cirebon (IAI BBC), 80% are the Y-generation. The characters of this generation are very sensitive to technology and communication, meaning that they have advantages in the field of information and knowledge development. In response to this, IAI BBC is required to innovate in the teaching and learning process in accordance with these characteristics. Combining conventional learning with non-conventional or e-learning is one solution in the framework of Y-generation learning. eCampus application is a platform that provides menus for learning (academic) and non-academic processes. By using the eCampus, students who are accustomed to using technology can access materials, lesson plans, discussions, assignments and exams that have been structured for each meeting so that it can make it easier to achieve the targets to be achieved in learning objectives. The use of e-learning through the eCampus IAI Bunga Bangsa Cirebon is a combination of face-to-face (offline) and online (online) or can be concluded as blended learning. This learning stands on an information technology infrastructure and can be done anytime and anywhere which has the characteristics of being open (open source) to users. ABSTRAK Perbedaan generasi menjadi salah satu subjek yang muncul dalam perkembangan dunia pendidikan, hal ini berdampak terhadap kepercayaan, nilai, budaya, perspektif, kegemaran, dan kemahiran yang berbeda terhadap kehidupan dan pekerjaan. Generasi yang lahir pada 1980 sampai 1995-an saat perkembangan teknologi sedemikian pesatnya disebut dengan generasi-Y. Berdasarkan data mahasiswa Institut Agama Islam Bunga Bangsa Cirebon (IAI BBC) 80% termasuk generasi-Y. Karakter dari generasi ini sangat peka terhadap teknologi dan komunikasi, artinya mereka memiliki keunggulan dalam bidang informasi dan perkembangan pengetahuan. Menyikapi hal tersebut IAI BBC dituntut inovasi dalam proses belajar mengajar yang sesuai dengan karakter tersebut. Mengkombinasikan pembelajaran konvensional dengan non konvensional atau e-learning merupakan salah satu solusi dalam rangka pembelajaran pada generasi-Y. Aplikasi eCampus adalah platfrom yang menyediakan menu-menu untuk proses pembelajaran (akademik) dan non akademik. Dengan menggunakan aplikasi eCampus mahasiswa yang terbiasa menggunakan teknologi dapat mengakses materi, rencana pembelajaran, diskusi, tugas dan ujian yang sudah disusun dengan terstruktur setiap pertemuan sehingga dapat memudahkan dalam mencapai target yang ingin dicapai dalam tujuan pembelajaran. Penggunaan e-learning melalui eCampus IAI Bunga Bangsa Cirebon ini kombinasi tatap muka (luring) dengan online (daring) atau disimpulkan sebagai blended learning. Pembelajaran ini berdiri di atas infrastruktur teknologi informasi dan bisa dilakukan kapanpun dan dimanapun yang memiliki karakteristik yang terbuka (open source) bagi pengguna.